Integrated optimal control and parameter estimation algorithms for discrete-time nonlinear stochastic dynamical systems - Kek, Sie Long, 1976-; Mohd. Ismail Abd. Aziz, supervisor; Rohanin Ahmad, supervisor; Teo, Kok Lay; Fakulti Sains (2011)
Thesis (Ph.D (Matematik)) - Universiti Teknologi Malaysia, 2011